Developing a Mindset for Rapid Incremental Innovation (Review of Knowledge Economy, 2014)
Why do so many complicated crises flourish in a world that has the capabilities to solve these significant challenges? Why has it taken so long for the world’s developed economies to grow after a deep recession? What are the keys to solving major problems and to grow economies? It seems the means are there, but not the will to understand how we must go about realizing more from the vast human and technical capacity available today. We posit that the path to improvement is for more individuals and organizations to innovate; that is, to improve effectiveness and efficiency in all they do. This improvement starts and ends with individual mindsets. This paper addresses these issues in a novel and non-academic way. We do this in large part to stress a point that must be made in order for academics to become and remain innovative.